HUBUNGAN PENDIDIKAN DAN PELATIHAN JUMANTIK DENGAN KEBERHASILAN PROGRAM PSN DI KELURAHAN TANAH KALIKEDINDING KOTA SURABAYA - Emy Muliawati (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to know relation of last education and status of training who monitor larvae with successful of Mosquito Eradication Program. Methods: This research is analitic observasional research with use cross-sectional study approach. The population of this research is 251 cadres and 72 persons of them are responden by simple random sample technic.  Independent variables of this research are last education, knowledge, attitude, behavior’s cadre and dependent variable is successful of Mosquito Eradication Program. Results: Result of this research have analyzed using Chi Square Test with 90% precision and α = 0,05 for 72 respondensshow that variable wich have relation with successful of Mosquito Eradication Program is status of training (P-value=0,041) with contingency coeficient as big as 0,255 wich mean have low relation. Variables wich haven’t relation with successful of Mosquito Eradication Program are last education (P-value=0,093); knowledge (P-value=1,000); attitude (P-value=1,000) and behavior’s cadre (P-value=0,675). Conclusion: Conclusion of this research is no relation between being active cadre who monitor larvae with successful of Mosquito Eradication Program.